POLA PENGOBATAN TUBERKULOSIS PARU DI BALAI BESAR KESEHATAN PARU MASYARAKAT MAKASSAR PERIODE JANUARI – JUNI 2011 - Hendra Herman; Bayu Putra; Citra Dana (Fakultas Farmasi UMI, 2013)
The research was about Tuberculosis Drugs Using System in the Balai Besar Kesehatan Paru Masyarakat Makassar (BBKPM) Period January 2011 – June 2011. The aim of this research was to describe about using system so obtained TBC drugs which used in the Tuberculosis Drugs Using-System in the Balai Besar Kesehatan Paru Masyarakat Makassar (BBKPM) Period January 2011 – June 2011. The data taking prospectly via all the tuberculosis patient medical record in the Tuberculosis Drugs Using System in the Balai Besar Kesehatan Paru Masyarakat Makassar (BBKPM) Period January 2011 – June 2011 obtained 30 patients. The result of this research can be concluded that from the regiment side, about 96,7% Tuberculosis patients which treatment in the Balai Besar Kesehatan Paru Masyarakat Makassar (BBKPM) Period January 2011 – June 2011 were category 1 and the residual was category 3. While the side of combination with the other drug, giving combination dominated about 96,7%. While if the give single drug about 3,3%. The frequency of the other drug usage was dextromethorphan about 90% and the smaller was pyridoxin about 10%.Key Word : Using System, Tuberculosis Drugs, BBKPM